Microencapsulated eáential oils active against indianmeal moth - Sanna Paáino, G.=700 1 Bazzoni, E.; Moretti, M.D.L.
(Es, En)
ilus., 19 ref.
Keywords: ROSMARINUS; ACEITES ESENCIALES; FORMULACIONES; PLODIA INTERPUNCTELLA; ESPAÑA